Fast and Sensitive: Automated Point-of-Care Urine Dips. Issue 10 (October 2020) - Malia, Laurie; Strumph, Kaitlin; Smith, Sharon; Brancato, John; Johnson, Stephanie T.; Chicaiza, Henry
Abstract : Objective: Point-of-care (POC) urine dipstick is a highly used test in the pediatric emergency department (PED) owing to its fast turn-around time and inexpensive cost. Past studies have shown hand-held urine dipsticks and automated urinalysis in children younger than 48 months to be sensitive predictors for urinary tract infection (UTI). It is hypothesized that POC dip testing is as accurate as laboratory urinalysis in the diagnosis of UTI. Methods: A retrospective chart review was conducted on patients (aged birth through 18 years) presenting to a PED between January 2015 and December 2015. Eligible subjects included those that had a POC dip, laboratory urinalysis (lab UA), and urine culture performed during their PED visit. Subjects were selected, using a random number generator; 334 charts were selected. A positive POC dip was defined as having a positive leukocyte esterase or the presence of nitrites. A positive lab UA was defined as having a positive leukocyte esterase, nitrites, or greater than 10 white blood cells per high-power field. Urine culture was used as the criterion standard for comparison. Results: A total of 334 subjects' charts were reviewed. Sensitivity and specificity of the POC dip were 91.4% (95% confidence interval [CI], 76.9%–98.2%) and 63.9% (95% CI, 57.2%–69.3%); lab UA, 91.4% (95% CI, 76.9%–98.2%) and 63.9% (95% CI, 58.2%–69.3%); and lab dip, 88.6% (95% CI, 73.3%–96.8%) and 65.6% (95% CI, 59.9%–70.9%). Conclusions: Point-of-care dips are as sensitive in detecting UTI as the lab UA. A prospective study could allow for further demographic evaluation of POC dip diagnosed UTI.